Influenza Vaccination of Pregnant Women and Protection of Their Infants - Madhi, Shabir A; Cutland, Clare L; Kuwanda, Locadiah; Weinberg, Adriana; Hugo, Andrea; Jones, Stephanie; Adrian, Peter V; van Niekerk, Nadia; Treurnicht, Florette; Ortiz, Justin R; Venter, Marietjie; Violari, Avy; et al. (The New England journal of medicine, 2014)
In two trials of a trivalent inactivated influenza vaccine in pregnant women in South Africa, HIV-infected and HIV-uninfected vaccine recipients had increased influenza antibody titers and decreased influenza attack rates. Pregnant women are designated as a priority group for seasonal influenza vaccination by the World Health Organization (WHO) 1 because of their heightened susceptibility to severe influenza from the second trimester to the early postpartum period. 2 , 3 Since pregnancy is associated with immunomodulation, including the attenuation of cell-mediated immune responses, 4 the efficacy of inactivated influenza vaccine (IIV) in pregnant women may differ from its efficacy in healthy nonpregnant women and in men. 5 This difference in vaccine efficacy could be further accentuated in pregnant women infected with the human immunodeficiency virus (HIV), who are at heightened risk for severe influenza illness 6 – . . .